Pelatihan Penulisan Artikel Bagi Mahasiswa IAI Sumbar - Mega Adyna Movitaria; Edriagus Saputra; Melda Delvia; Syamsurizal (Yayasan Literasi Sains Indonesia, 2022)
The purpose of this service is to determine the scientific writing ability of students at IAI West Sumatra and the factors that influence it. The lack of student knowledge about article writing and how to publish inspiring articles is done by community service to convey socialization and provide training on writing this article. If students understand the importance of writing articles in the academic world, it is hoped that they will be motivated to write scientific articles and publish scientific articles as contributors to the development of science, and can practice it directly by utilizing journals managed by the campus. Based on the partner's main problem, namely the lack of knowledge of students about writing scientific articles, the solution offered to partners is to provide materials related to writing scientific articles, reference managers, submit and publish articles to increase student understanding in writing scientific articles. The methods used are presentation, questions and answers, and simulations. The target to be achieved in this community service activity is the introduction of article writing for West Sumatra IAI students. The output target of this program is to increase the ability to write articles for IAI West Sumatra students and the ability to publish articles in national journals. The data sources studied were IAI West Sumatra students.